The Effectiveness of FluentU Application on Students’ Vocabulary Mastery - Rahmadini, Fani; Ramadhani, Syafitri (Universitas Negeri Padang, 2024)
The purpose of this research is to identify the effectiveness of FluentU application in improving students’ vocabulary mastery at the tenth-grade students. This is a pre-experimental research design. The population of the study was tenth-grade students at SMA N 2 Sungai Limau. The population consist of 171 students that are classified into five classes. X FASE E 5 was selected as a sample through cluster random sampling method. The total number of the students in this class is 34 students. The research is conducted in six meetings. The researcher used pre-test and post-test to collect the data. The instrument of this research is vocabulary test. There are 25 questions with multiple choice questions. The result of the study shows that the significant value of the two-tailed paired sample t-test was less than 0.05. It means that the null hypothesis (H0) in this research was rejected and the alternative hypothesis (H1) was accepted. It proved that the use of FluentU application to improve students’ vocabulary mastery is effective.